2010
DOI: 10.1017/s1047951110001848
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiac surgery in trisomy 18 patients

Abstract: Cardiac surgery contributed to increased survival rate but not the rate of discharge alive in trisomy 18 patients. Cardiac surgery could not prevent all the trisomy 18 patients from death. The indication of cardiac surgery should be carefully individualised to improve the quality of life in trisomy 18 patients and concerned surrounding people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 13 publications
1
51
0
Order By: Relevance
“…A Japanese study of 34 patients with T18 reported 22% two-year survival following corrective or palliative cardiac surgery, compared to 9% survival with only medical therapy [7]. Similarly, improved survival with surgical management has been reported by other small studies [8, 9].…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…A Japanese study of 34 patients with T18 reported 22% two-year survival following corrective or palliative cardiac surgery, compared to 9% survival with only medical therapy [7]. Similarly, improved survival with surgical management has been reported by other small studies [8, 9].…”
mentioning
confidence: 75%
“…Studies published in the past decade suggest that survival in children with T13 and T18 may be longer after intervention for CHD [710]. A Japanese study of 34 patients with T18 reported 22% two-year survival following corrective or palliative cardiac surgery, compared to 9% survival with only medical therapy [7].…”
mentioning
confidence: 99%
“…The present study was one of the few in the literature to evaluate the association of different subgroups of patients with CHDs with other clinical data, in regards to survival. Muneuchi et al [2011] classified the CHDs in complex and not complex abnormalities based on presence of concomitant lesions, differently from us. However, no difference in survival was observed between these kinds of defects in both studies.…”
Section: To the Editormentioning
confidence: 98%
“…Different factors have been associated with this poor prognosis, and congenital heart defects (CHDs) stand out as a common and important feature; in recent studies they have been pointed as the main cause of death of patients in the setting of intensive treatment [Kosho et al, 2006;Kaneko et al, 2008]. However, there is a scarcity of studies in the literature evaluating if there is a difference, concerning survival, among the different subgroups of patients with trisomy 18 and CHDs [Niedrist et al, 2006;Muneuchi et al, 2011]. Thus, the aim of our study was to verify frequency, types, and prognosis of CHDs in a Brazilian series of patients with trisomy 18.…”
Section: To the Editormentioning
confidence: 99%
“…however, new studies have demonstrated that good outcomes can be achieved with surgery in these patients and have shifted the discussion to how surgery can positively affect patient's quality of life [10]. Given the growing body of evidence demonstrating the feasibility of operative interventions in these patients, this study examines our institution's experience with ES and PS in the setting of comorbid CHD and presents the outcomes of surgical versus expectant management.…”
Section: Introductionmentioning
confidence: 99%